The rose in my garden - Lobel, Arnold; Lobel, Anita (New York, NY : Greenwillow Books, 1984)
A variety of flowers grows near the hollyhocks that give shade to the bee that sleeps on the only rose in a garden.
Wilson's Children.
Elem. School Library Collection.
School Library Journal.
4.1
K-3
Keywords: Flowers -- Fiction; Roses -- Fiction; Bees -- Fiction; Stories in rhyme; Flowers -- Fiction; Roses -- Fiction; Bees -- Fiction; Stories in rhyme; Flowers -- Fiction; Roses -- Fiction; Bees -- Fiction; Stories in rhyme